Management of educators and educational staff - Maftuhah Maftuhah; Amanta Annajma Khaularahma; Yovie Shafa Aulia Maymalaputri; Nazwa Aulia; Taufiqurrahman Taufiqurrahman (JURNAL PENDIDIKAN IPS, 2025)
Educator and education personnel management is a key component in improving the quality of education, involving systematic resource management from planning to supervision. This process influences the quality of learning, work motivation, and student achievement. This study aims to examine the concept, urgency, service areas, and processes of educator and education personnel management using qualitative literature study methods. The results indicate that professional management, including adaptive and continuous training, and attention to the psychological and professional dimensions of educators, is crucial in facing the challenges of the digital era.